Bank Syariah Indonesia’s Strategy Increases Sharia Financial Literacy to Optimize Public Interest in Sharia Bank Products - Sugiarti, Dian; Ulfah, Indar Fauziah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the strategy of Bank Syariah Indonesia (BSI) in increasing the community's Sharia financial literacy and implementing POJK Number 3 of 2023, as well as analyzing the influence of Sharia financial literacy on public interest in Sharia banking products. This research uses qualitative descriptive methods through interviews to identify Bank Syariah Indonesia's strategy for increasing Sharia financial literacy and uses quantitative methods to measure the level of Sharia financial literacy of the community and their interest in Sharia banking products. The respondents in this research were MSMEs with a total of 50 respondents. Then the data was analyzed using regression analysis. The results of this research show that Bank Syariah Indonesia is implementing several strategies to increase Sharia financial literacy, such as collaborating with educational institutions, government institutions, and associations, and through the BSI benefit program. Bank Syariah Indonesia's implementation of sharia financial literacy is following POJK Number 3 of 2023, namely through financial education and the development of sharia financial literacy infrastructure. Islamic financial literacy has a significant positive influence on interest in Islamic banking products.